EFEKTIVITAS APLIKASI GAME KAHOOT DALAM MENINGKATKAN MOTIVASIDAN HASIL BELAJAR SISWA PADA MATERI MATEMATIKADI SEKOLAH DASAR - Apriliyanti Muzayanati; Maemonah; Putri Puspitasari (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
Learning success cannot be separated from students’ interest and motivation toward mathematics learning. During the pandemic, teachers were required to be creative in fostering students’ learning motivation, one of which was the use of the Kahoot game. Kahoot is easy to use for upper-grade elementary school students, easily accessible, and allows students to work on questions interactively. In addition, the game provides scores and rankings that can trigger students to achieve higher results. For this reason, this study used Kahoot in mathematics learning. The researcher aimed to determine the effectiveness of Kahoot in increasing students’ motivation and learning outcomes in elementary schools. This study employed a quasi-experimental design using descriptive quantitative methods. The results revealed that Kahoot increased students’ learning motivation and learning outcomes. The increase in motivation was evident from students’ happiness and interest when using Kahoot. As students became more interested in the game, their learning motivation increased, as shown by a significance value of 0.048. This indicated that there was an improvement in motivation. Furthermore, the improvement in learning outcomes was proven through pretest and posttest results analyzed using a paired sample test. The significance value obtained was 0.000, which is less than 0.05, indicating a significant effect of the treatment on each variable. Thus, Kahoot was effectively used in mathematics learning, as evidenced by questionnaire results, students’ motivation, and improved learning outcomes.